ANALISIS LAPORAN KEUANGAN PERUSAHAAN INDUSTRI WADAH DAN KEMASAN YANG TERDAFTAR DI BEI TAHUN 2020-2024 - Yasinta, Syafa Salsabila; Prasetyo, Agung Slamet (Universitas Sarjanawiyata Tamansiswa, 2025)
As the foundation for other downstream businesses and a driver of national economic progress, Indonesia's packaging and container sector necessitates a thorough assessment of its financial health using financial ratio analysis. The aim of this study is to examine how profitability, liquidity, and solvency ratios affect the financial performance of companies in the container and packaging sector that are listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. Financial statements obtained from the official IDX website serve as secondary data for this investigation. Twenty container and packaging industry companies registered on the IDX make up the study's population, while 14 companies chosen through purposive sampling make up the sample. The data analysis method in this study is panel data regression analysis using Eviews 12 software. The regression model used in this study is the Random Effect Model, with partial results indicate that profitability significantly and favorably affects financial performance, while solvency significantly and negatively affects financial performance and liquidity has no effect on financial performance. Concurrently, the three ratios have an 87.74% impact on financial performance, with other factors accounting for the remaining percentage.